A inovação nas micro, pequenas e médias empresas sindicalizadas do arranjo produtivo local de Ubá-MG e região - Lacerda, Pítias Teodoro (2005)
The purpose of the current research was to verify how the Local Productive Enterprise (LPE) in Ubá-MG and surrounding areas contribute to the process of innovation and this one to the improvement of the global results of the trade union companies which are part of it. With regards to the methodology, it is a research of an exploiting and quantity nature. It is a poll survey whose data has been collected based on a non-probability sample formed by 43 companies. The main conclusion is that among the companies that have been interviewed, those which have the widest range of innovation are the ones that have experienced the most outstanding results and at the same time they are the group of companies which together seek for common solutions. This verification meets the main characteristics of a local productive enterprise: the accomplishment of group activities seeking solutions for the common issues means that the LPE contributes to the results of the companies which are part of it in such a way that it creates an appropriate environment for mutual cooperation. Moreover, with the achieved results from the project one can state that the intervention actions for the development of the LPE´s can be better oriented and it is expected that they are effective considering that there are still other peculiarities besides the accomplishment of partnership activities such as the capacity and the time of the company formation, the manager´s age and education which can be somehow associated with the innovation and the results that they can provide the companies.